Is Serum Vitamin D a Determinant of Carpal Tunnel Syndrome Severity? A Cross-Sectional Observational Study - Rachmat Saleh Eka Putra; Syarif Indra; Lydia Susanti; Yuliarni Syafrita; Restu Susanti; Reno Bestari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Carpal tunnel syndrome (CTS) represents one of the most frequently encountered compressive neuropathies affecting the upper extremities. Emerging evidence suggests a potential link between vitamin D status and CTS incidence and severity, with vitamin D deficiency proposed as an independent risk factor influencing symptom severity. This study aimed to investigate the association between serum 25-hydroxyvitamin D levels and the electrophysiologically determined severity of CTS in a cohort of patients in Padang, Indonesia. Methods: This cross-sectional observational study was conducted over eight months, from July 2024 to February 2025, at the Neurological Polyclinic of Dr. M. Djamil General Hospital Padang. Patients diagnosed with CTS based on clinical presentation and confirmed by nerve conduction studies (NCS) were consecutively enrolled. Exclusion criteria were applied to ensure a homogenous study population. Serum 25-hydroxyvitamin D levels were quantified using the Enzyme-Linked Immunosorbent Assay (ELISA) method. CTS severity was categorized as mild, moderate, or severe based on standardized NCS parameters. The association between serum 25-hydroxyvitamin D levels and CTS severity grades was analyzed using the Kruskal-Wallis test, with a p-value < 0.05 considered statistically significant. Results: A total of 45 subjects meeting the inclusion criteria were included in the final analysis. The median age of the participants was 36 years (range 20-71), with a predominance of female patients (n=37, 82.2%). The mean Body Mass Index (BMI) was 24.1 ± 4.66 kg/m². Based on NCS findings, CTS severity was classified as mild in 20 patients (44.4%), moderate in 16 patients (35.6%), and severe in 9 patients (20%). The overall median serum 25-hydroxyvitamin D level across all CTS patients was 27.80 ng/mL (range 10.4 - 278.4 ng/mL). When stratified by severity, the median vitamin D levels were 23.75 ng/mL for mild CTS, 27.95 ng/mL for moderate CTS, and 37.50 ng/mL for severe CTS. Despite an apparent trend of increasing median vitamin D levels with increasing CTS severity, the Kruskal-Wallis test revealed no statistically significant association between serum 25-hydroxyvitamin D levels and the severity of CTS (p = 0.094). Conclusion: Serum 25-hydroxyvitamin D levels were not found to be significantly associated with the severity of carpal tunnel syndrome as determined by nerve conduction studies. Further research with larger sample sizes and diverse populations is warranted to clarify the potential role of vitamin D in the pathophysiology and clinical presentation of CTS.